STUDY FORMS OF FEMINISM IN SHORT STORY COLLECTION PARODIA BY ISTIFARI HASAN - Barkhoya, Ahmad Asif (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
The focus of this research actually lies on the descriptive qualitative research model with a socialfeminist approach. By using the object collection of Parodia short stories written by Istifari Hasan, researcherstried to show the forms of feminism contained therein. From sources that have been collected in parallel,researchers found that there are feminism forms contained in a collection of Parodia short stories by IstifariHasan that are full of social values in real community life in socializing, especially for women. In this case,researchers also aim to cultivate the analysis of short stories in the area of Indonesian literature. With theshort story analysis that carries the theme of feminism, it is hoped that readers or literary connoisseurs can getcloser to understanding the meaning or message of the author. After the researcher found a form of feminismin a collection of Parodia short stories written by Istifari Hasan, the researcher tried to look back at the realitythat occurred in the life of the surrounding community which was not much different from the eventscontained in literary works, especially short stories which are indeed often the object of social criticism forwriters.